2009
DOI: 10.1074/jbc.m808656200
|View full text |Cite
|
Sign up to set email alerts
|

HSF1-mediated BAG3 Expression Attenuates Apoptosis in 4-Hydroxynonenal-treated Colon Cancer Cells via Stabilization of Anti-apoptotic Bcl-2 Proteins

Abstract: 4-Hydroxynonenal (HNE) is a pro-apoptotic electrophile generated during the spontaneous decomposition of oxidized lipids. We have previously shown that HNE activates the transcription factor, heat shock factor 1 (HSF1), and promotes cytoprotective heat shock gene expression and that silencing HSF1 sensitizes the colon cancer cell line RKO to HNE-induced apoptosis. Here we report a reduction in the anti-apoptotic proteins Bcl-X L , Mcl-1, and Bcl-2 in HSF1-silenced RKO cells, and we examine the underlying mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 52 publications
6
127
2
1
Order By: Relevance
“…Indeed, it has previously been shown that BAG3 can physically associate with a number of proteins potentially involved in tumorigenesis (e.g., PLC-γ, Akt, Bcl-XL, HspB8) (12,13,43,44); however, no correlation between these interactions and the prosurvival effect of BAG3 has been provided. Similarly, although it has been clearly demonstrated that BAG3 can affect the levels and/or activity of a number of other proteins potentially involved in tumor transformation (e.g., p27, Rac1, the focal adhesion proteins FAK and paxillin, the matricellular signal regulator CCN1) (45)(46)(47)(48), neither a clear mechanism through which BAG3 regulates them nor a clear causative role of BAG3 antiapoptotic activity has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has previously been shown that BAG3 can physically associate with a number of proteins potentially involved in tumorigenesis (e.g., PLC-γ, Akt, Bcl-XL, HspB8) (12,13,43,44); however, no correlation between these interactions and the prosurvival effect of BAG3 has been provided. Similarly, although it has been clearly demonstrated that BAG3 can affect the levels and/or activity of a number of other proteins potentially involved in tumor transformation (e.g., p27, Rac1, the focal adhesion proteins FAK and paxillin, the matricellular signal regulator CCN1) (45)(46)(47)(48), neither a clear mechanism through which BAG3 regulates them nor a clear causative role of BAG3 antiapoptotic activity has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…107 Further experiments have demonstrated that the stabilization of Bcl2 anti-apoptotic proteins (like Mcl1, Bcl-xL and Bcl2) is dependent on the induction of BAG3 (Bcl2-associated athanogene domaine 3) that interacts with Hsp70 and Bcl-xL. 117 The degree of protection gained by this pathway is thought to be superior to the protection afforded by the detoxification pathways like Nrf2. 116 HNE Assault: The Choice to Stay Alivey Under Conditions HNE as a cell cycle brake.…”
Section: Hne Self Limits Apoptosis: Keeping Cool Under Pressurementioning
confidence: 99%
“…Resulting data were analysed by using Expression Console software (Affymetrix) with default RMA parameters. Genes regulated by DAS were determined with a 2-fold change (37).…”
Section: Flow Cytometric Assay For the Production Of Camentioning
confidence: 99%